2004
DOI: 10.1207/s15328015tlm1603_13
|View full text |Cite
|
Sign up to set email alerts
|

The Departmental Advisor's Effect on Medical Students' Confidence When the Advisor Evaluates or Recruits for Their Own Program During the Match

Abstract: Applicants whose departmental advisors serve on a residency selection committee have less confidence in the advising relationship. These interactions may have adverse effects on the clinical and professional development of medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…4 The limited evidence from learners' perspective shows that learners are less comfortable with advisors who have a role in assessment than those who do not and that such an assessment role can influence a learner's willingness to be open and honest in an advising relationship. 2 This is the first study we are aware of that examines opinions of faculty leaders on the perceived COIs among medical educator roles and the acceptability of assessing students within the context of learning communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The limited evidence from learners' perspective shows that learners are less comfortable with advisors who have a role in assessment than those who do not and that such an assessment role can influence a learner's willingness to be open and honest in an advising relationship. 2 This is the first study we are aware of that examines opinions of faculty leaders on the perceived COIs among medical educator roles and the acceptability of assessing students within the context of learning communities.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, students with advisors in clinical specialties who also served on a residency selection committee expressed discomfort with the advising relationship and admitted to being more likely to make misleading statements about training program preferences than if the advisor had no role in resident selection. 2 Likewise, some have argued that student affairs officers should not oversee the preparation of the Medical Student Performance Evaluation (MSPE) document that compiles assessment data for graduating students. The concern raised is that such an arrangement may discourage students from seeking out “sensitive health services” if the student affairs office is the conduit by which students access those resources.…”
mentioning
confidence: 99%
“…This can, however, create an inherent internal conflict of the program director in the process of advising. A study by Miller in 2004 demonstrated less confidence in the student when the advisor sat on the residency selection committee ( 7 ). If a dual advisor system is instead employed (program director and medical student advisor), studies have shown low levels of congruity of opinions between these two groups ( 8 ).…”
Section: Discussionmentioning
confidence: 99%